Analysis of the Effectiveness of PBL-Oriented Interactive Electronic Student Activity Sheets Development on the Material of Factors Affecting Chemical Equilibrium to Improve Students Science Literacy Skills - Mufidah, Rachma; Dwiningsih, Kusumawati (Jurnal Pijar Mipa, 2024)
The science literacy skills of Indonesian students are still low based on the results of PISA 2022. Chemical equilibrium material is very important, and understanding chemical equilibrium is a prerequisite for understanding subsequent materials. One of the efforts to improve understanding of chemical equilibrium material is applying a student-centred learning model, the PBL model. PBL can also improve students' science literacy skills. Thus, research was conducted to develop PBL-oriented interactive electronic student activity sheets on chemical equilibrium material to improve students' science literacy skills. This research aims to describe the effectiveness of interactive E-LAPD as a learning media for improving students' science literacy skills. Research and development (Research and Development) is the type of research used.  The research design used in this research is the 4-D model development research design according to Thiagarajan's 4-D model, which consists of the define, design, develop, and disseminate stages. The instrument used in this research is a pretest and posttest sheet of science literacy skills to measure students' science literacy skills. This research used a limited trial with a one-group pretest-posttest research design. The limited trial was conducted at SMAN 1 Kedamean with 36 class XI MIPA 3 students. The effectiveness results analyzed using the paired sample t-test obtained a p-value of 0.000, which indicates that the posttest value after learning using interactive E-LAPD is greater than the pretest value before learning using interactive E-LAPD. Thus, PBL-oriented Interactive E-LAPD can be said to improve students' science literacy skills.